Concerns regarding SARS-CoV-2 JN.1 mutations should be raised - Roney, Miah; Huq, A. K. M. Moyeenul; Mohd Fadhlizil Fasihi, Mohd Aluwi (Springer Nature, 2024)
JN.1 is a new variant of SARS-CoV-2 which is a subvariant of Omicron (BA.2.86) was first discovered in the USA in September 2023. The virus’s capacity to spread and elude the immune system may be impacted by a single alteration in the spike protein, which serves as its distinguishing feature. JN.1 has been classified as an interesting variety by the World Health Organisation. JN.1 might lead to a rise in infections, or its possible influence on public health is yet premature. Current immunisations, examinations, and therapies are still anticipated to combat JN.1.